Khulu’ dalam Perspektif Hadis Tematik - Sabari Sabari; Erwin Hafid; Abustani Ilyas (Al-fiqh, 2026)
Khulu’ is one of the divorce mechanisms in Islam that grants a wife the right to terminate the marital bond by providing certain compensation to the husband. This study aims to analyze the concept of khulu’ based on thematically relevant hadiths of the Prophet Muhammad (peace be upon him), as well as to explain the normative, procedural, and moral foundations of its practice in Islam. The method employed is library research with a qualitative approach, involving the collection and analysis of hadiths on khulu’ found in various hadith compilations, complemented by an examination of classical fiqh literature to explore the views of the four major schools of Islamic jurisprudence (Hanafi, Maliki, Shafi‘i, and Hanbali), as well as contemporary scholars. The collected data are then classified thematically, analyzed comparatively, and interpreted contextually. The findings indicate that khulu’, from the perspective of thematic hadith, is understood as a form of Islamic justice that provides protection for women in disharmonious marital relationships. The hadiths on khulu’ emphasize mutual consent, the obligation to return the dowry, and the prohibition of abuse of rights by either spouse. Therefore, khulu’ is not merely a legal instrument of divorce, but also a conflict resolution mechanism oriented toward public welfare (maṣlaḥah) and the balance of rights within Muslim families.